Optimazed Mutual Funds Investment Portfolio Through Good Corporate Governance And Financial Banking Performance - Azis, Musdalifah; Nadir, Maryam; Purnamasari, dan Ike (International Journal of Economics and Financial Issues, 2017)
The achievement of optimize mutual funds portfolio can increase financial performance banking be better and so their relations between mutual funds manager. Data is collected from the stock share portfolio report that are presented on record the balance of each company mutual funds report in partnership with banks as a sales agent of the mutual funds, with use linear programming application software POM for window and multiple regression application SPSS. The research results obtained the equity composition is Optimize investment portfolio mutual funds this could be achieved by 6-7 kind of mutual funds stock, 9-10 kind of balanced mutual funds, 13-14 kind of mutual funds fixed income and 12-13 kind of money market mutual funds, mean there are 40-44 kind of portfolio mutual funds that can be maximized distribution of a product mutual funds it by bank as dealers products the mutual funds can optimize mutual funds portfolio up to value of IDR 1263.66 through banking financial performance. Keywords: mutual funds portfolio, finance banking performance, investment manager JEL Classifications: G2, G11